Highly stable silver nanohybrid electrocatalysts for the oxygen reduction reaction. Issue 20 (21st February 2022) - Lenne, Quentin; Retout, Maurice; Gosselin, Bryan; Bruylants, Gilles; Jabin, Ivan; Hamon, Jonathan; Lagrost, Corinne; Leroux, Yann R.
Abstract : Deliberate functionalization of silver nanoparticles with a monolayer of calix[4]arenes leads to a highly stable electrocatalyst toward the ORR. Abstract : Silver nanoparticles (AgNPs) were deliberately functionalized via aryl diazonium chemistry with a monolayer of calix[4]arenes. The resulting nanohybrids show high efficiency and high selectivity toward the ORR in alkaline media along with an exceptional durability and a high methanol tolerance.